1992
DOI: 10.1128/jvi.66.5.2617-2630.1992
|View full text |Cite
|
Sign up to set email alerts
|

Molecular attenuation of vaccinia virus: mutant generation and animal characterization

Abstract: These studies demonstrated that the inbred BALB/c mouse strain can be optimized for the assessment of vaccinia virus virulence, growth, and spread from the site of inoculation and immune protection from a lethal vaccinia virus challenge. The studies established that manipulation of the vaccinia virus genome generated mutants exhibiting a wide range of attenuated phenotypes. The nine NYCBH vaccinia virus mutants had intracranial 50% lethal doses that ranged from 2 to >7 log1o units. The decreased neurovirulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
4

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 24 publications
(24 reference statements)
3
38
0
4
Order By: Relevance
“…HA is found on the plasma membrane of infected cells and the envelope of extracellular virus (EEV) but is absent from intracellular mature virus (IMV), the most abundant infectious forms of infectious virions [33,34]. Several studies showed that the loss of HA is associated with the reduced virulence of vaccinia viruses [17,23,35]. For example, MVA has the major deletion III in the HA promoter region [36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HA is found on the plasma membrane of infected cells and the envelope of extracellular virus (EEV) but is absent from intracellular mature virus (IMV), the most abundant infectious forms of infectious virions [33,34]. Several studies showed that the loss of HA is associated with the reduced virulence of vaccinia viruses [17,23,35]. For example, MVA has the major deletion III in the HA promoter region [36].…”
Section: Discussionmentioning
confidence: 99%
“…The inbred BALB/c mouse was chosen for the assessment of MVTT ZCI virulence using a previously described method [17,18]. Groups of five-week old mice were inoculated intranasally with 0, 10 4 , 10 5 or 10 6 PFU of MVTT ZCI in 20 ul of PBS.…”
Section: The Virulence Of Mvtt Zci In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…The in vivo virulence of MVTT 2-GFP was evaluated in inbred BALB/c mice using methods as described previously (Lee et al, 1992;Betakova et al, 2000;Zhang et al, 2000). The viral virulence was first determined by the daily measurement of body weight change for a period of 10 days after the animals were inoculated with the virus via the intranasal route.…”
Section: In Vivo Virulence Of Mvtt 2-gfp In Micementioning
confidence: 99%